The Relationship Between Boredom Proneness and Phubbing Behavior in Adolescents - Putri Ningrum Afifah; Niken Titi Pratitis; Rahma Kusumandari (Psikologi Prima, 2026)
This study specifically aimed to investigate and determine the relationship between the variable of boredom proneness and phubbing behavior among adolescent subjects. The methodological approach applied in this study utilized a quantitative research design, involving 120 adolescent participants. In the subject selection process, the sampling technique employed was quota sampling, with inclusion criteria specifying participant ages ranging from 15 to 18 years old. Furthermore, the data analysis phase was conducted by applying a non-parametric statistical technique using the Spearman's Rho correlation test; the findings of this study indicated a positive relationship between boredom proneness and phubbing behavior in adolescents. The implications of these results indicated that the higher the level of boredom proneness experienced by adolescents, the higher the intensity of the phubbing behavior exhibited. Conversely, the lower the level of boredom proneness possessed by adolescents, the lower the tendency for phubbing behavior to occur.